Developing E-Module-Based PJBL Oriented with STEM on SPLDV Material to Improve Problem-Solving Skills - Ni Wayan Sri Maeti; Gede Suweken; I Nengah Suparta (Universitas Pendidikan Ganesha, 2025)
The lack of instructional media that effectively integrates Project-Based Learning (PjBL) and STEM approaches in mathematics learning, particularly on the topic of Systems of Linear Equations in Two Variables (SPLDV), poses a challenge in enhancing students’ problem-solving skills. This study aims to explore the development process and examine the quality of a PjBL-based e-module oriented with STEM to improve students’ mathematical problem-solving abilities. This research adopts a research and development (R&D) design, comprising three main phases: preliminary research, prototyping, and evaluation. The participants included 90 students selected through random sampling and 2 teachers selected through purposive sampling. Data were collected using observation, interviews, document analysis, and tests, with instruments such as observation sheets, interview guides, field notes, and problem-solving test items. The data were analyzed qualitatively using Miles and Huberman’s technique and quantitatively through descriptive statistics. The results indicate that the developed e-module meets the criteria of being valid, practical, and effective for mathematics instruction. These findings suggest that integrating PjBL and STEM into e-modules offers an innovative solution for enhancing students’ problem-solving skills in mathematics.